Gene Loss and Horizontal Gene Transfer Contributed to the Genome Evolution of the Extreme Acidophile “Ferrovum” - Ullrich, Sophie R.; González, Carolina; Poehlein, Anja; Tischler, Judith S.; Daniel, Rolf; Schlömann, Michael; Holmes, David S.; Mühling, Martin (Frontiers in Microbiology, 2016)
Acid mine drainage (AMD), associated with active and abandoned mining sites, is a habitat for acidophilic microorganisms that gain energy from the oxidation of reduced sulfur compounds and ferrous iron and that thrive at pH below 4. Members of the recently proposed genus “Ferrovum” are the first acidophilic iron oxidizers to be described within the Betaproteobacteria. Although they have been detected as typical community members in AMD habitats worldwide, knowledge of their phylogenetic and metabolic diversity is scarce. Genomics approaches appear to be most promising in addressing this lacuna since isolation and cultivation of “Ferrovum” has proven to be extremely difficult and has so far only been successful for the designated type strain “Ferrovum myxofaciens” P3G. In this study, the genomes of two novel strains of “Ferrovum” (PN-J185 and Z-31) derived from water samples of a mine water treatment plant were sequenced. These genomes were compared with those of “Ferrovum” sp. JA12 that also originated from the mine water treatment plant, and of the type strain (P3G). Phylogenomic scrutiny suggests that the four strains represent three “Ferrovum” species that cluster in two groups (1 and 2). Comprehensive analysis of their predicted metabolic pathways revealed that these groups harbor characteristic metabolic profiles, notably with respect to motility, chemotaxis, nitrogen metabolism, biofilm formation and their potential strategies to cope with the acidic environment. For example, while the “F. myxofaciens” strains (group 1) appear to be motile and diazotrophic, the non-motile group 2 strains have the predicted potential to use a greater variety of fixed nitrogen sources. Furthermore, analysis of their genome synteny provides first insights into their genome evolution, suggesting that horizontal gene transfer and genome reduction in the group 2 strains by loss of genes encoding complete metabolic pathways or physiological features contributed to the observed diversification.